The Effectiveness of The Implementation of The e-Court Justice System and The Impact on Administrative Court in Indonesia (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2022)
Using the e-Court system in the Administrative Court aims to create a simple, fast, and low-cost judicial environment under the constitutional mandate where law enforcement and justice need to be carried out as efficiently as possible, both in terms of faster time and cheaper cost. However, in its implementation, it is necessary to conduct a study on the effectiveness and impact of technological renewal in the form of e-Court in the administrative court realm to evaluate the existing system. This research is normative legal research using statutory, comparative, and conceptual approaches. In contrast, the legal materials used are primary, secondary, and tertiary legal materials using documentary study techniques. From this study, it was found that the e-Court system can optimize the realization of the principles of good general justice in Indonesia, but in its implementation it is not yet optimal in terms of implementation and technically so that innovation and further improvements are still needed.